Abstraction, desalination and recharge method to control seawater intrusion into unconfined coastal aquifers - S. Sadjad Mehdizadeh; S. Badaruddin; S. Khatibi (Global Journal of Environmental Science and Management)
In this study, abstraction, desalination and recharge method and SEAWAT numerical model are used to investigate seawater intrusion repulsion in a hypothetical two-dimensional coastal aquifer to understand the relation of seawater intrusion with abstraction, desalination and recharge parameters (i.e. abstraction/recharge rate, wells distance and depth). Abstraction, desalination and recharge consists of abstraction and desalination of brackish water and recharge of desalinated water. The results of different defined scenarios showed that increase of recharge rate has a significant effect on the seawater intrusion mitigation (e.g. more than 80% variation in saline water volume) while the increase of abstraction rate does not have specific impact on seawater recession (e.g. less than 3% variation in toe position). The method efficiency in reducing seawater intrusion is increased when freshwater is recharged by well at outside of saltwater wedge and close to its toe position. Moreover, it is shown that the abstraction, desalination and recharge performance has slightly improved when the recharge and extraction wells are placed deeper into aquifer and close to aquifer bottom (almost 15% for all characteristics of salt wedge). Ultimately, dilution of saline water with recharged freshwater will widen the mixing zone but as salt wedge recedes toward the sea simultaneously, the mixing zone thickness cannot follow the steady reduction trend.